Improving Support Systems for Cocoa Farmers beyond Cocoa Swollen Shoot Virus Disease Infestation - Tetteh Adesah; Collins Osei; Enoch Kwame Tham-Agyekum; John-Eudes Andivi Bakang (Jurnal Social Economic of Agriculture, 2023)
Cocoa swollen shoot virus disease (CSSVD) has severely hampered the production of cocoa in Ghana since pre-colonial days. The Ghana Cocoa Board has put several measures in place to support cocoa farmers in the fight against the CSSVD. This present study captures how the CSSVD affects cocoa farmers and the support systems for such situations. Using a survey design, the study employed the multi-stage sampling technique to select 413 cocoa farmers. A structured questionnaire was used to seek information from the cocoa farmers. A multiple linear regression model was estimated to analyse the data. The CSSVD affects the living standards of cocoa farmers through their economic wellbeing, thus, household income and assets accumulation. The social wellbeing of farmers is also affected by the CSSVD through their socio-cultural (participation in cooperatives and communal activities) and educational activities (participation in extension education activities). The implication is that the current support systems given to cocoa farmers after being affected by the CSSVD need to be strengthened, enhanced and made holistic to cover their economic and social wellbeing. Economic and social interventions aimed at increasing the resilience of cocoa farmers in the face of the CSSVD will be helpful in this direction.